Does a Leapfrogging Growth Strategy Raise Growth Rate? Some International Evidence - Zhi Wang; Shang-Jin Wei; Anna Wong (Asian Development Bank (ADB), 2010)
While openness to trade is a well-recognized hallmark of the Asian growth model, another component of the model is a leapfrogging strategy—the use of policies to guide industrial structural transformation ahead of a country's factor endowment. Does the leapfrogging strategy work? Opinions vary but the evidence is scarce in part because it is more difficult to measure the degree of leapfrogging than the extent of trade openness. We undertake a systematic look at the evidence both across countries and subregions within a large regional Asian economy to assess the efficacy of such a strategy. We conclude that there is no strong and robust evidence that this strategy works reliably.
hdl:11540/1959
Keywords: O20; O40; 330; growth; trade openness; leapfrogging